The impact of the American Civil War on city growth - Maria Vera-Cabello; Marcos Sanso-Navarro; Fernando Sanz (European Regional Science Association (ERSA), 2011)
This paper analyzes the persistence of the shock caused by the American Civil War on the relative city size distribution of the United States. Our fi ndings suggest that the effects of this shock were permanent, which sharply contrasts with previous results regarding World War II for Japanese and German cities. It should be taken into account that the conflict considered in this paper took place at an earlier stage of the industrialization and urbanization processes. Moreover, our results are determined by the fact that the battles were fought in the open field, not in urban areas. Some related evidence regarding the presence of a safe harbour effect is reported.
Keywords: 330